Immigration Wage Impacts by Origin - Bernt Bratsberg; Oddbjørn Raaum; Marianne Røed; Pål Schøne (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2010)
We estimate the direct partial wage effect for native workers of an immigrant-induced increase in labor supply, using longitudinal records drawn from Norwegian registers and the national skill cell approach of Borjas (2003). Our results show overall negative wage impacts for both men and women. Focusing on differential wage impacts by immigrant origin, we find that immigrant inflows from the neighboring Nordic countries have more negative wage effects than inflows from developing countries. The pattern is consistent with factor demand theory if natives and other Nordic citizens are close substitutes. We also find that impact estimates, particularly for inflows from nearby countries, are sensitive to accounting for selective native attrition and within-skill group variation in demand and supply conditions.
Keywords: 330